THE PERCEPTION OF JUSTICE IN JUVENILE CRIMINAL PROCEEDINGS: AN ETHICAL AND MORAL REVIEW - Utami, Made Sri Dewi; Gorda, Anak Agung Ayu Ngurah Tini Rusmini (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The phenomenon of justice in the juvenile criminal justice system is a complex issue that requires a balance between law enforcement and protection of children's rights, where approaches that focus on rehabilitation and recovery must be prioritized considering that children are individuals who are still in the process of forming identity and morals. This research aims to analyze the perception of justice in the handling of juvenile criminal cases from the perspective of ethics and morality in Indonesia and identify factors that influence the realization of justice in the juvenile criminal justice system. This research uses a normative legal research method with a conceptual approach that analyzes primary, secondary, and tertiary legal materials through literature studies, and uses qualitative descriptive analysis to examine perceptions of justice in the juvenile criminal justice system from an ethical and moral perspective. The results showed that the perception of justice in the handling of juvenile criminal cases in Indonesia is in a tug of war between restorative justice approaches (which are regulated in the SPPA Law) and retributive (which are still strong in society), where the realization of justice is influenced by six main factors, namely the application of the principles of restorative justice, the socio-environmental conditions of children, the role of law enforcement officials in the implementation of diversion, gaps in policy and practice in the field, public perceptions of children in conflict with the law, and ethical-moral considerations related to the stage of development and the best interests of children